Forest Management for Carbon Sequestration and Climate Adaptation - Todd A Ontl; Maria K Janowiak; Christopher W Swanston; Jad Daley; Stephen Handler; Meredith Cornett; Steve Hagenbuch; Cathy Handrick; Liza Mccarthy; Nancy Patch (Journal of Forestry, 2020)
The importance of forests for sequestering carbon has created widespread interest among land managers for identifying actions that maintain or enhance carbon storage in forests. Managing for forest carbon under changing climatic conditions underscores a need for resources that help identify adaptation actions that align with carbon management. We developed the Forest Carbon Management Menu to help translate broad carbon management concepts into actionable tactics that help managers reduce risk from expected climate impacts in order to meet desired management goals. We describe examples of real-world forest-management planning projects that integrate climate change information with this resource to identify actions that simultaneously benefit forest carbon along with other project goals. These examples highlight that the inclusion of information on climate vulnerability, considering the implications of management actions over extended timescales, and identifying co-benefits for other management goals can reveal important synergies in managing for carbon and climate adaptation.